Diary of a Wimpy Kid : Hard luck - Kinney, Jeff. (London : Penguin Books, 2015)
Mom's always saying that friends will come and go but family is forever. Well, if that's true, I could be in for a rough ride. Greg Heffley's on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg's life destined to be just another hard-luck story?